Анализ основы информационных компонент системы функционирования книжно-журнальных изданий с селективно изменяемым наполнением - Петриашвили, Г. (Моделювання та інформаційні технології, 2010)
This article describes the problem of the formal description of the information component of the information technology, methods for their transformation and analysis, based on the above concepts of the semantic parameters.